2013
DOI: 10.1007/s00384-013-1727-4
|View full text |Cite
|
Sign up to set email alerts
|

In vivo lymph node mapping and pattern of metastasis spread in locally advanced mid/low rectal cancer after neoadjuvant chemoradiotherapy

Abstract: The fat clearance technique should be the standard pathological examination in patients with RCs after CRT; N staging was improved by small lymph node identification. Lymph node metastases have a continuous spread through mesorectal sectors. Blue dye injection is effective in sentinel lymph node detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…LNs <5 mm in size are called micro LNs, and they are susceptible to being overlooked during the detection phase. 36 It has been reported that nearly half of resected LNs are micro LNs, and nearly half of metastatic LNs are micro LNs. 15 Therefore, harvesting an adequate number of micro LNs is important for accurate tumor staging.…”
Section: Discussionmentioning
confidence: 99%
“…LNs <5 mm in size are called micro LNs, and they are susceptible to being overlooked during the detection phase. 36 It has been reported that nearly half of resected LNs are micro LNs, and nearly half of metastatic LNs are micro LNs. 15 Therefore, harvesting an adequate number of micro LNs is important for accurate tumor staging.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that carbon nanoparticle tracer technology can help solve these problems. It has been report that that CNs in the operation is helpful for detect the sentinel lymph node, because the dyeing time is short, and the lymph node staining of each station is insufficient, so, injecting CNs into tumor area 1 -3 days before operation may help the lymph node at each stage fully stained, and these lymph nodes can be used to clean the lymph nodes at all sites and avoid missing cancerous tissue [26]. For the staining lymph nodes other than the third station, the lymph nodes need not be routinely cleaned, but can be excised and sent to rapid frozen pathological examination [27].…”
Section: Discussionmentioning
confidence: 99%
“…The rationale of the technique is based on information provided by anatomical and cadaveric studies describing rectal lymphatic mapping, according to which the lymphatic drainage is directed in a centripetal, caudo‐cranial pathway. Aberrant drainage to pelvic nodes is rare (< 5%), even in case of ultralow rectal cancer . Considering the minimally invasive approach that is used to perform ELRR, and the anatomical relationship between the rectum and mesorectum, NGME is necessarily performed by two sequential phases, ex vivo and in vivo .…”
Section: Discussionmentioning
confidence: 99%